Gold nanoparticles capped with sulfamethoxazole-ovotransferrin conjugate as a potential nanomedicine for the treatment of microbial infections - Ibrahim, Hisham R.; Kubo, Takemichi (Journal of Medical Science, 2025)
Introduction. Although sulfonamide antibiotics are potent antimicrobial agents against bacterial infections, their water insolubility and toxicity at high doses limit their therapeutic efficacy. This study explores a potent anti-infection drug-delivery system using gold nanoparticles (gNPs) capped with ovotransferrin (OTf) as a targeting carrier and solubilising agent for sulfamethoxazole (SMZ) antibiotic. Materials and methods. The OTf was conjugated with sulfamethoxazole OTf(SMZ) at pH 9.0 for 24 h at 29°C. The conjugate (OTf(SMZ)) or free OTf was added to the gold chloride solution containing sodium citrate as a reducing agent, and then stirred for 24 h at 37˚C. The gold nanoparticle (GNP) formulations were purified by gel filtration. The gNP formulations and their individual components (free OTf, SMZ, and gNP tested separately) were evaluated against several microbial strains, including drug-resistant Salmonella, and against bacteria that infect human cells intracellularly. Results. The gold nanoparticle capped with OTf loaded with SMZ [OTf(SMZ)-gNP] showed superior microbicidal activity against several bacterial strains and the fungi Candida albicans compared to the activities of gNP capped with OTf alone [OTf-gNP] or the individual agents. The wild-type Salmonella enteritidis, which encodes the multidrug efflux channel TolC, becomes susceptible to both OTf(SMZ)-gNP and OTf-gNP nano-formulation but not to their separate components. However, the tolC-knockout Salmonella enteritidis mutant strain was susceptible only to the OTf(SMZ)-gNP, indicating the ability of this nanoformulation to deliver the antibiotic SMZ into bacterial cells through self-promoted uptake. The OTf(SMZ)-gNP efficiently killed pathogens intracellularly infecting human colon carcinoma cells. Conclusions. The results demonstrate that OTf(SMZ)-gNP nanomaterials can mediate the endocytosis of SMZ, making them suitable for targeting bacterial infections, including those that have acquired antibiotic resistance. The study highlights the potential of OTf-capped nanomaterials that can be engineered to enhance the potency of hydrophobic antibiotics for treating infectious diseases.